KESİRLİ ANALİZ YARDIMIYLA İKİNCİ MERTEBEDEN SİNGÜLER DİFERANSİYEL DENKLEMLERİN ÇÖZÜMLERİ - ÜRÜNVEREN, NESİME (Fırat Üniveristesi, 2023)
Matematiksel analizin bir kolu olan kesirli analiz, türev ve integralin keyfi mertebelere genişletilmiş halidir. Fen ve mühendislikte geniş uygulama alanına sahiptir. Bu tezde, ilk olarak kesirli analiz üzerine yapılan çalışmalar, ilgili tanım ve teoremler verildi. Daha sonra, Coulomb potansiyeline sahip ?-boyutlu kesirli uzayda Schrödinger denklemi ele alınıp, değişkenlerine ayırma yöntemiyle elde edilen radyal denkleminin kesirli analiz yardımıyla açık çözümleri elde edilmiştir.

Fractional analysis, which is a branch of mathematical analysis, is the extension of derivative and integral to arbitrary orders. It has a wide application area in science and engineering. In this thesis,initially, studies on fractional analysis, related definitions and theorems are given respectively. Then, the Schrödinger equation in ?-dimensional fractional space with Coulomb potential is considered and the explicit solutions of the radial equation are obtained by the separation method with the help of fractional analysis.
Solutions of second order singular differential equations using fractional analysis
Keywords: Matematik